Keluarga Sebagai Gereja Pertama: Peran Pendidikan Agama Kristen dalam Membentuk Spiritualitas Generasi Digital - Raskita Enjelika Manik; Herda Sitanggang; Delima Hot Marito Hasugian; Fretty Solafide Matanari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The family is the primary place where the faith of children and adolescents is formed, especially in the digital age, which is rife with information and moral dilemmas. Home is more than just a place to live; it is where children learn Christian values ​​through parental example, prayer, discussion, and attention. With the digital generation growing up with rapid access to the internet and social media, it is crucial for parents to ensure that technology becomes a tool for growth, not a threat to faith. This study analyzed literature on Christian religious education in families, children's spiritual development, and challenges in the digital age. The results show that strong emotional connections and active parental involvement in daily faith education can significantly shape children's character and spirituality. The family is the primary foundation in preparing a wise digital generation, firmly rooted in Christ, and able to navigate changing times without losing their faith identity.